Interest to be Teacher and Cumulative Grade Point Average (CGPA) Analyzed by the Admissions of UIN Syarif Hidayatullah Jakarta - Ahmad Sofyan (TARBIYA: Journal of Education in Muslim Society, 2016)
Abstract This study aims to explore the interest to be teacher for FITK (Faculty of Tarbiyah and Teachers Training) students associated with the other types of variables such as gender, origin of High School, Cumulative Grade Point Average (CGPA), and the admission types to UIN Syarif Hidayatullah Jakarta. A survey method was administered to students in Science Education department from three courses, by200 people as samples. The instruments were an open questionnaire to record the factual data and an enclosed questionnaire to asses their interest. The data analysis employed the descriptive and inferential techniques. The results showed that the students’ interest to be teacher is quite high. There was no interest different between male and female students based on the educational background and the entrance types to UIN. Even though based on gender women’s CGPA was relatively higher than men’s, generally, there was no distinction of students CGPA based on the educational background, and admission of UIN Jakarta.Abstrak Penelitian ini bertujuan untuk mengetahui minat mahasiswa FITK menjadi guru ditinjau dari berbagai latar belakang seperti jenis kelamin, asal SLTA, indeks Prestasi Kumulatif (IPK), dan jalur masuk UIN. Syarif Hidayatullah Jakarta. Penelitian ini difokuskan pada mahasiswa Jurusan Pendidikan IPA, dari 3 angkatan dengan sample data sebanyak 200 orang. Instrumen yang digunakan adalah kuesioner terbuka untuk mencatat data faktual dan kuesioner tertutup untuk menilai  minat mahasiswa.  Teknik analisis data ini bersifat deskriptif dan inferensial. Hasil penelitian menunjukan bahwa minat mahsiswa menjadi guru cukup tinggi. Tidak ditemukan perbedaan minat antara mahasiswa dan mahasiswi yang didasarkan pada asal sekolah SLTA dan jalur masuk UIN. Meskipun berdasarkan  pengelompokan IPK  sesuai jenis kelamin yang relatif lebih tinggi adalah perempuan, secara umum, tidak terdapat perbedaan IPK mahasiswa berdasarkan latar belakang pendidikan dan  jalur masuk UIN. How to Cite : Ahmad Sofyan. (2016). Interest to be Teacher and Cumulative Grade Point Average (CGPA) Analyzed by the Admissions of Uin Jakarta. TARBIYA: Journal Of Education In Muslim Society, 3(1), 107-120. doi:10.15408/tjems.v3i1.3407. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v3i1.3407